Reversal pattern of health inequality: New evidence from a large-scale national survey in Japan. Issue 11 (November 2020) - Takaku, Reo
Highlights: High-SES workers in Japan belong to a lifetime employment system (LES). Health status and income level are compared between LES workers and others. LES workers have 36% more household savings at their middle age. Despite their high income, they are more likely to develop diabetes and hyperlipidemia. Also, cancer risk increases among female LES workers. Abstract: Despite extensive evidence for a positive association between socio-economic status (SES) and health, some studies have shown that this well-established pattern of health inequality is reversed in Japan due to individuals of high SES working in stressful workplace environments. High-SES workers in Japan generally belong to a lifetime employment system (LES) in large companies. Thus, in this study, individuals who had been working for a single company for several decades at the time of a 2005 survey (LES workers) were compared with other workers by logistic regression and ordinary least squares regression. These analyses showed that LES workers had 36% more household savings. However, despite their relatively high income, the LES workers were more likely to develop diabetes (odds ratio 1.134: 95% CI 1.022–1.259) and hyperlipidemia (odds ratio 1.184: 95% CI 1.079–1.300). Among women, LES workers were at higher risk of developing cancer (odds ratio 1.570: 95% CI 1.174–2.098). In addition, these effects were consistently found in subsequent surveys between 2006 and 2015, suggesting that the LES had long-term adverse effects on health. These results taken together show that career trajectory is an important determinant of health inequality in the elderly population.